THE CHANGE OF TOTAL PROTEIN FRACTION OF MUSCLE TISSUE OF PORK WITH BIO- AND PHYSICO-CHEMICAL SPECIFIC IN THE PROCESS OF COOKING AT DIFFERENT TEMPERATURES - O. Shalimova (Russian Journal of Agricultural and Socio-Economic Sciences, 2012)
The character of changes in total protein fraction of muscle tissue of pork with PSE defects in the process of cooking at temperatures ranging from 40 to 72 g.C in steps of 2 g.C is investigated. Our studies have revealed differences in the change of state the total fraction of muscle proteins with defects PSE pork during cooking.